Exogenous Melatonin Improves Drought Tolerance by Regulating the Antioxidant Defense System and Photosynthetic Efficiency in Fodder Soybean Seedings - Qianhan Zhao; Xueling Zheng; Chen Wang; Qinyi Wang; Qiyun Wei; Xiashun Liu; Yujiao Liu; Along Chen; Jia Jiang; Xueying Zhao; Tiantian He; Jiayi Qi; et al. (Plants)
Fodder soybean (Glycine max L.) with high protein and yield is a popular forage grass in northeast China. Seasonal drought inhibits its growth and development during seedling stage. The objective of this study was to observe morpho-physiological changes in fodder soybean seedlings under melatonin (MT) treatments and identify appropriate concentration to alleviate the drought damage. Two varieties commonly used in northeast China were treated with 0, 50, 100, and 150 μM melatonin at soil water content of 30%. The results indicated that applying melatonin enhanced height, biomass and altered root morphology of fodder soybean seedlings under water-deficient conditions. The treatments with melatonin at different concentrations significantly reduced the contents of H2O2, O2− and MDA, while boosting the capacity of the antioxidant defense system and the content of osmotic adjustment substances. Meanwhile, increases in light energy capture and transmission efficiency were observed. Furthermore, treatment with melatonin regulated the expression levels of genes associated with photosynthesis and the antioxidant defense system. Notably, 100 μM melatonin treatment produced the most favorable effect in all treatments under drought conditions. These research results provide new information for enhancing the drought tolerance of fodder soybean using chemical measures.